Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Produk Nichoa dengan Metode SEM-PLS di Jawa Tengah - Salsabila Aprilia Hudoyo; Erlyna Wida Riptanti; Umi Barokah (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This research purports to assign the marketing mix's effect on price, promotion, product, and place on consumer decisions in purchasing Nichoa products in Central Java. This study is causal-comparative research. The study location was chosen by purposive method with the reasoning that the average expenditure per capita of the population of Central Java in the food and beverage category has increased during the last three years. The research was conducted from February to March 2022. The latent variables in this research are product, place, price, promotion, and purchasing decisions. The total sample is 120 respondents by purposive sampling technique. An analysis method used is SEM-Partial Least Square (PLS). The output represents a positive impact on purchasing decisions and a significant effect on the product, place, and price variables on consumer decisions in purchasing Nichola products. However, there is an insignificant impact on the promotion variable, but it has a positive value on consumer decisions in purchasing Nichoa products. This point that Nichoa must pay attention to the marketing mix carried out, in terms of product, price, promotion, and place aspects, to be able to answer consumer needs so that it can influence consumers to buy Nichoa products more than once.